Digital technology and productivity of informal enterprises: Empirical evidence from Nigeria - Michael Danquah; Solomon Owusu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
The lingering policy dilemma facing many governments in sub-Saharan Africa in recent years is what can be done in the short to medium term to boost the output and incomes of individuals and enterprises in the informal sector, given the size and persistence of the sector in the region. In this paper we examine the structural impact of access and usage of digital technology by informal enterprises on labour productivity. Using a sample of non-farm informal enterprises in Nigeria, we employ IV LASSO techniques to carry out our analysis. The structural parameters of our IV LASSO estimates show that labour productivity is significantly higher for enterprises that use digital technology than for non-users. Further analysis reveals that benefits arise more strongly in larger enterprises in the upper segment of the informal sector. Our findings have key implications for the ongoing discussion on the role of digital technology and government regulatory and policy frameworks for ICT in the region.
Keywords: D22; O17; O33; O55; 330; digital technologies; informal sector; productivity; IV LASSO; Nigeria